Development of Microsoft Access for using in Library - Zakariah, Askari (IAI Al-Mawaddah Warrahmah Kolaka, 2022)
The object of research in the preparation of this paper is the Microsoft Access 2010 database application system which is a combination of several previous tasks that have been made in the form of a Microsoft Access-based database application design. Microsoft Access could be applied on Library for arrange, search, and documented visitor, donation of book and list of book data